Considerations on Plato’s Timaeus - Escobar Moncada, Jairo (Estudios de Filosofía, 1995)
The aim of this article is to demonstrate that Plato’s Timaeus is made up of four essential moments and that only through joint consideration of all these may we reach an adequate combination so as to open up the dialogue’s enigmas. These four moments are: 1: The problem of the divine and its relationship with the world. 2: The relationship between Eikos and Logos, the Cosmos and Philosophy. 3: The theory of elements and their relation with space. 4: The problem of time and necessity.